EP420/#949 Postoperative venous thromboembolism risk in patients with vulvar dysplasia and carcinoma, a national surgical quality improvement program study. (4th December 2022) - Wagner, Vincent; Felix, Ashley; Meade, Caitlin; Chambers, Laura
Abstract : Objectives: Due to the relatively low prevalence of vulvar dysplasia and cancer, the risk factors associated with VTE in this population are poorly understood. We aimed to analyze the risk factors associated with VTE in women undergoing surgery for vulvar dysplasia and carcinoma. Methods: Patients who underwent vulvar procedures for dysplasia or carcinoma were collected from the National Surgical Quality Improvement Program database (NSQIP). Baseline demographics and clinical characteristics were compared between patients that did and did not have a VTE. Descriptive and univariable analyses were performed. Results: Between 2014 and 2020, 1414 patients undergoing vulvar procedures for dysplasia and carcinoma were included; 521 (37.1%), 438 (31.2%), 267 (19.0%) and 171 (12.2%) underwent simple vulvectomy, radical vulvectomy, radical vulvectomy with bilateral inguinofemoral lymphadenectomy or radical vulvectomy with unilateral lymphadenectomy respectively. No patients (0/521) who underwent simple vulvectomy had a VTE. VTE rate was 1.13% (5/443) in radical vulvectomy alone and 1.35% with lymphadenectomy (0.74% for bilateral and 2.29% unilateral). No patients that underwent sentinel lymphadenectomy had a VTE (0/19). Univariate analysis revealed functional dependency, operation time, wound disruption and postoperative infection (including UTI, sepsis and deep SSI) as risk factors for VTE. Conclusions: Patients with vulvar dysplasia undergoing simple vulvectomy have low risk for VTE, those with carcinoma undergoing radical vulvectomy have a moderate risk of VTE. The risk factors for VTE include functional dependency, longer operating time and postoperative infections. Sentinel lymphadenectomy appears to carry a low risk of VTE.